Pengaruh Pemberian Ekstrak Biji Kopi Robusta (Coffea canephora) Lampung terhadap Aktivitas Enzim Katalase Hippocampus Tikus Putih (Rattus norvegicus) Jantan Galur Sprague dawley yang Diinduksi Monosodium Glutamat - Syazili Mustofa; Ni Sayu Putu Desya Laksmi Putri; Lucky Togihon; Wayan Ferly Aryana; Rizki Putra Sanjaya; Tito Tri Saputra (Majority, 2023)
Almost 60 million people worldwide have recovered from pulmonary tuberculosis since 2000, but many of them develop post-tuberculous lung disease. The disease results from a complex interaction between the disease-causing organism, the host, and environmental factors, and this affects the long-term airway. People with this disease have a shorter life expectancy and an increased risk of tuberculosis recurrence. Bronchiectasis is a disease of the dilation of the bronchial tubes which is characterized by decreased mucociliary transport function. It can also be caused by a bacterial infection with Post Tuberculosis Obstructive Syndrome (SOPT). SOPT is a lung disorder characterized by chronic airway obstruction due to complications arising from post-treatment pulmonary tuberculosis. This case describes a patient with bronchiectasis and SOPT who came with symptoms of shortness of breath accompanied by a long cough. From the results of the physical examination and supporting examinations, a working diagnosis was obtained in the form of infected brochiectasis accompanied by post-tuberculosis obstructive syndrome. The patient was then given therapy in the form of oxygenation, nebulized bronchodilators, corticosteroid injections, and antibiotics. In addition, patients are also given chest physiotherapy and a high-calorie, high-protein diet.